2022
DOI: 10.3390/biomedicines10051113
|View full text |Cite
|
Sign up to set email alerts
|

Alloferon Affects the Chemosensitivity of Pancreatic Cancer by Regulating the Expression of SLC6A14

Abstract: Pancreatic cancer (PCa), one of the most malignant solid tumors, has a high mortality rate. Although there have been many trials of chemotherapeutic drugs such as gemcitabine, the mortality rates remain significantly higher than for other types of cancer. Therefore, more effective ways of improving conventional therapy for PCa are needed. Cancer cells take up large amounts of glutamine to drive their rapid proliferation. Recent studies show that the amino acid transporter SLC6A14 is upregulated in some cancers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Alloferon is known to provide support for the low toxicity of gemcitabine in the treatment of patients with advanced PCa, showing high efficacy as an adjuvant in the treatment of PCa (Min et al, 2002). Exposure of Panc-1 and AsPC-1 cells to alloferon increased the chemosensitivity of the cells to gemcitabine, and combined treatment with gemcitabine and alloferon increased apoptosis in Panc-1 cells (Jo et al, 2022). Considering the contribution of alloferon in the gemcitabine chemotherapy for PCa, it might be a useful adjuvant not only for PCa but also for other types of cancer.…”
Section: Combination Of Alloferon and Chemotherapy: Enhancing Antitum...mentioning
confidence: 95%
See 1 more Smart Citation
“…Alloferon is known to provide support for the low toxicity of gemcitabine in the treatment of patients with advanced PCa, showing high efficacy as an adjuvant in the treatment of PCa (Min et al, 2002). Exposure of Panc-1 and AsPC-1 cells to alloferon increased the chemosensitivity of the cells to gemcitabine, and combined treatment with gemcitabine and alloferon increased apoptosis in Panc-1 cells (Jo et al, 2022). Considering the contribution of alloferon in the gemcitabine chemotherapy for PCa, it might be a useful adjuvant not only for PCa but also for other types of cancer.…”
Section: Combination Of Alloferon and Chemotherapy: Enhancing Antitum...mentioning
confidence: 95%
“…Due to the role of SLC6A14 in tumor progression, its inhibition may aid tumor regression and treatment. Alloferon effectively inhibited the expression of the glutamine transporter SLC6A14 in pancreatic cancer cells, thereby reducing the uptake of glutamine into the cells (Jo et al, 2022). Chernysh et al discovered following the administration of alloferon, insignificant clusters of cancer cells were eliminated, and the growth of primary tumors visibly declined.…”
Section: Antitumor Activity Of Alloferonmentioning
confidence: 99%
“…It possesses antitumor properties. Jo et al demonstrated that alloferon substantially decreases the expression of ATB 0,+ in PC cells and reduces ATB 0,+mediated Gln uptake, which in turn inhibits PC cell growth and proliferation [66].…”
Section: Asct2 Inhibitorsmentioning
confidence: 99%
“…They also exhibit antitumor and antiviral properties. Alloferon-1 has been implicated in regulating acute and chronic inflammatory responses in various diseases, such as skin and corneal epithelial cells, rheumatoid arthritis, and asthma (Ryu et al, 2008;Zhang et al, 2014;Jo et al, 2022;Lee et al, 2023). Cantharidin, a toxic compound extracted from blister beetles such as Mylabris phalerata and M. cichorii, has demonstrated promising antitumor effects by inhibiting the proteins phosphatase 1 (PP1) and phosphatase 2A (PP2A).…”
Section: Pharmaceuticalsmentioning
confidence: 99%